Freshwater fisheries management (Fishing News Books, 1995)
The new edition of this widely successful text continues to offer a wealth of essential information and practical guidance for all involved in freshwater fisheries management in temperate regions. Whilst the whole text has been fully revised and many sections have been completely rewritten to cover the many advances and developments of the last decade, the clarity of presentation and accessibility of style, hallmarks of the previous edition, are retained.